2009
DOI: 10.1073/pnas.0906722106
|View full text |Cite
|
Sign up to set email alerts
|

Simple cellular and network control principles govern complex patterns of motor behavior

Abstract: The vertebrate central nervous system is organized in modules that independently execute sophisticated tasks. Such modules are flexibly controlled and operate with a considerable degree of autonomy. One example is locomotion generated by spinal central pattern generator networks (CPGs) that shape the detailed motor output. The level of activity is controlled from brainstem locomotor command centers, which in turn, are under the control of the basal ganglia. By using a biophysically detailed, full-scale computa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
101
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 45 publications
0
101
1
Order By: Relevance
“…Another possible mechanism for the reversal of swim direction in lampreys was suggested by Kozlov et al (2009) within the framework of the trailing-oscillator model. In a simulation study these authors demonstrated that a chain of coupled oscillators, generating FS, could be switched to the generation of BS when excitability in only a few rostral segments was decreased.…”
Section: Possible Spinal Targets Of Different Groups Of Rs Neuronsmentioning
confidence: 99%
“…Another possible mechanism for the reversal of swim direction in lampreys was suggested by Kozlov et al (2009) within the framework of the trailing-oscillator model. In a simulation study these authors demonstrated that a chain of coupled oscillators, generating FS, could be switched to the generation of BS when excitability in only a few rostral segments was decreased.…”
Section: Possible Spinal Targets Of Different Groups Of Rs Neuronsmentioning
confidence: 99%
“…Biologically detailed lamprey spinal cell models (26) are used in large-scale simulations of the locomotor network (7) to replicate electric activity in command centers and the spinal cord. A mechanical model of swimming (27,28) is used for a quantitative evaluation of the locomotor response.…”
Section: Significancementioning
confidence: 99%
“…One example is the reticulospinal neurons in the brainstem that serve as the major interface between higher level commands and the networks in the spinal cord in all vertebrates from lamprey to primates (4)(5)(6). In this study, we investigate the motor system of the lamprey, belonging to the most ancient group of vertebrates that has been investigated in considerable detail not only at the brainstem-spinal cord level but also with regard to the forebrain systems underlying the control of action (2,7,8). A bilateral symmetric activation of reticulospinal neurons will activate the locomotor networks in the spinal cord, resulting in coordinated swimming movements (2,(9)(10)(11).…”
mentioning
confidence: 99%
“…The selection and timing of modular activation is dependent on task biomechanics Ivanenko et al 2003;McGowan et al 2010;Neptune et al 2009;Ting and Macpherson 2005) and sensory feedback (Cheung et al 2005;Kargo and Giszter 2008). Cortical activation also may influence modular control (Gentner and Classen 2006;Holdefer and Miller 2002;Kozlov et al 2009). …”
mentioning
confidence: 99%